2000
DOI: 10.1128/mcb.20.4.1162-1169.2000
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Protein Synthesis Is Initiated from the Internal Ribosome Entry Segment during Apoptosis

Abstract: Recent studies have shown that during apoptosis protein synthesis is inhibited and that this is in part due to the proteolytic cleavage of eukaryotic initiation factor 4G (eIF4G). Initiation of translation can occur either by a cap-dependent mechanism or by internal ribosome entry. The latter mechanism is dependent on a complex structural element located in the 5 untranslated region of the mRNA which is termed an internal ribosome entry segment (IRES). In general, IRES-mediated translation does not require eIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(206 citation statements)
references
References 66 publications
10
194
0
2
Order By: Relevance
“…23 In a study to determine the mechanisms used to maintain c-Myc expression during apoptosis, HeLa cells were treated with TRAIL and this resulted in apoptosis of 90% of the cells. In this situation, c-Myc protein levels were maintained at the same levels as untreated cells and the data strongly suggest that under these conditions recruitment of the c-myc message to ribosome by the c-myc IRES allows the levels of c-Myc protein to be maintained 16,24 In contrast, even though Apaf-1 translation is solely initiated by internal ribosome entry, 25 the only situation where a small increase in Apaf-1 IRES function was observed was following genotoxic stress. 26 Given the importance of Apaf-1 during brain development, it is possible that the Apaf-1 IRES is required for the expression of this protein in the developing brain.…”
Section: During Apoptosis There Is a Switch Between Cap-dependent Andmentioning
confidence: 74%
See 2 more Smart Citations
“…23 In a study to determine the mechanisms used to maintain c-Myc expression during apoptosis, HeLa cells were treated with TRAIL and this resulted in apoptosis of 90% of the cells. In this situation, c-Myc protein levels were maintained at the same levels as untreated cells and the data strongly suggest that under these conditions recruitment of the c-myc message to ribosome by the c-myc IRES allows the levels of c-Myc protein to be maintained 16,24 In contrast, even though Apaf-1 translation is solely initiated by internal ribosome entry, 25 the only situation where a small increase in Apaf-1 IRES function was observed was following genotoxic stress. 26 Given the importance of Apaf-1 during brain development, it is possible that the Apaf-1 IRES is required for the expression of this protein in the developing brain.…”
Section: During Apoptosis There Is a Switch Between Cap-dependent Andmentioning
confidence: 74%
“…In each of these diverse conditions, it has been found that approximately 3% of the messages remain associated with the polysomes including c-myc mRNA. 33 However, while there is some overlap between the genes found associated, many of the mRNAs identified are distinct, suggesting that up to 10% of all cellular mRNAs can be translated by an alternative mechanism from global regulation. In addition, as not all mRNAs that are selected for translation during conditions of pathophysiological stress contain IRESs, it is likely that other hitherto unidentified mechanisms exist to recruit the ribosome.…”
Section: Analysis Of Mrnas That Remain Polysomally Associated During mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these cellular IRESes are utilized during different stress conditions such as hypoxia or heat shock. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] In light of the above, a major question that became of interest to the cell death community, and will be addressed in detail in this issue of CDD, is whether translational switches are part of the PCD process, and more specifically, whether a shift from cap-dependent to IRES-mediated translation occurs under certain settings of cell death. In fact, it turned out that induction of type I PCD, for example, is associated with a rapid and substantial shut-off of overall protein synthesis in the cell.…”
Section: Switching the Initiation Of Protein Synthesis From Cap-depenmentioning
confidence: 99%
“…Extensive work over the past several years revealed that this group comprise mRNAs encoding both proapoptotic proteins such as DAP5, c-Myc and Apaf-1, and antiapoptotic proteins such as XIAP and HIAP2, all of which harbor functional IRES elements within their 5 0 UTR, known as 'death IRESes'. 38,42,48,69,70 In theory, de novo synthesis of proapoptotic proteins provides positive feedback, reinforcing the death cascade. This might be especially important when dealing with short-lived protein products (as in the case of c-myc).…”
Section: Identification Of Dap5 Mrna Targetsmentioning
confidence: 99%